(untitled) (Research, Society and Development, 2021)
The growing rise of virtual social media has made it possible to extend sexual crimes against children and adolescents, which made it possible for the police officer infiltrated in this area. This scientific article provides the study of police operations that used virtual infiltration to combat sexual crimes against children and adolescents committed within the scope of the internet. The main objective of this research is to verify the efficiency of the digital infiltrated agent in the repression of these crimes. In order to achieve this goal, four federal police operations are studied from the technical perspective of two policemen and from the legal perception obtained from two judgments. The views of the two agents, who have the empirical knowledge of having acted in the reported investigations, allow an understanding of the modus operandi of virtual infiltration; and the analysis of the jurisdictional provisions demonstrates the way in which the investigated of the investigated operations were convicted. The article achieved its purpose by demonstrating the efficiency of the four police endeavors, as they achieved countless convictions and several rescues of minors in situations of vulnerability.